1995
DOI: 10.1093/eurheartj/16.suppl_c.59
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-mediated vasodilation during ACE inhibition

Abstract: ACE inhibitors are superior to other vasodilators in the treatment of congestive heart failure and may be advantageous in patients with myocardial infarction and hypertension. The mechanisms mediating these beneficial effects are not clear. The present article discusses the mechanisms leading to augmented release of endothelium-derived nitric oxide during ACE inhibition. Acute potentiation of bradykinin (Bk)-induced vasodilation was studied in rings of bovine and human coronary arteries mounted in organ chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In contrast, captopril has been reported to diminish contractile responses to PE in the presence of a functional endothelium in normal rats that is not mediated through bradykinin receptors 31 . In this respect, it has also been shown that ACE inhibitors potentiate the effects of bradykinin on endothelial cells by a local mechanism, probably independent of the degradation of bradykinin 11 . Other findings indicate that the effects of captopril are mediated not only via inhibition of the formation of vasoconstrictory angiotensin II, but also by accumulation of bradykinin, which stimulates the synthesis of vasodilatory NO 30 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, captopril has been reported to diminish contractile responses to PE in the presence of a functional endothelium in normal rats that is not mediated through bradykinin receptors 31 . In this respect, it has also been shown that ACE inhibitors potentiate the effects of bradykinin on endothelial cells by a local mechanism, probably independent of the degradation of bradykinin 11 . Other findings indicate that the effects of captopril are mediated not only via inhibition of the formation of vasoconstrictory angiotensin II, but also by accumulation of bradykinin, which stimulates the synthesis of vasodilatory NO 30 .…”
Section: Discussionmentioning
confidence: 98%
“…31 In this respect, it has also been shown that ACE inhibitors potentiate the effects of bradykinin on endothelial cells by a local mechanism, probably independent of the degradation of bradykinin. 11 Other findings indicate that the effects of captopril are mediated not only via inhibition of the formation of vasoconstrictory angiotensin II, but also by accumulation of bradykinin, which stimulates the synthesis of vasodilatory NO. 30 Meanwhile, ACE inhibitors were not able to alter NO synthesis by vascular smooth muscle cells under basal and interleukin-1␤-stimulated conditions in cultured rat vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hypertensive type 2 patients with diabetic nephropathy, lisinopril has been shown to improve endothelial dysfunction [9]. The mechanisms whereby ACEI improve endothelial function may involve sparing of bradykinin by ACEI and an antioxidant effect via decreased angiotensin II-mediated production of superoxide anion by membrane-bound oxidases [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible may involve sparing of bradykinin by ACE inhibitors [7][8][9][10][11][12], an antioxidant effect via decreased angiotensin II-mediated production of superoxide anion by membrane-bound oxidases [13][14][15] or other mechanisms [6]. Losartan, a drug which blocks angiotensin type 1 receptors, also improves resistance vessel endothelial function in subjects with Type II diabetes [16], suggesting that at least part of the beneficial effect of angiotensin II modulation is mediated through the angiotensin II\type 1 receptor pathway.…”
Section: Introductionmentioning
confidence: 99%